Sono vitali le varietà venete? - Ursini, Flavia (Quaderni Veneti, 2012)
The essay starts from the fact that the unesco Atlas of the World’s Languages in Danger classifies the different «Venetian variety» (the definition preferred to the one of Venetian «dialects» or «language») as a «vulnerable» variety, which is a better status than the one of other languages of the world. Using those data coming from the most recent surveys of the Istat («Italian National Institute of Statistics») Ursini describes the linguistic situation of the Northeast Italy which is characterised by the strong presence of any local variety and by a «double image»: on the one hand, the significant tradition of the native-speaking people and their huge proficiency; on the other one, the innovative trend of young people who re-discover their dialect and spread it, though in a reduced mass. Then, Ursini analyses the different public politics for preserving and promoting the so-called «weak» languages and proposes some remarks on their efficacy (sometimes very problematic).